Wizards of Waverly Place : the movie [videorecording (DVD)] - Lafferty, Kevin (Producer); Berendsen, Dan; Spiro, Lev L.; Gomez, Selena, 1992-; Henrie, David; Austin, Jake T. (Jake Toranzo), 1994-; Burgomaster, Kenneth; Hofeling, Mark (Disney DVD., 2009)
Follow the Russo family as they vacation at the Caribbean resort where Jerry and Theresa first met. Alex's mom makes her go on the family vacation - something Alex is not too pleased about. She conjures a spell that erases her parents' fateful first meeting and puts the Russo family's very existence in peril.